The Life of Lichen - James Stevenson; Lara B. Milligan; Jennifer L. Gillett-Kaufman (EDIS)
Lichen represent a fascinating combination of organisms working together to form some familiar and unfamiliar growths on a variety of substrates. This fact sheet hopes to define and explain these organisms.